Editorial - James Wilhelm; Boris Kühn; Antony Mason (Intergenerational Justice Review)
There exists a frequently unhelpful and rigidly formulated theoretical dichotomy in the intergenerational literature, which can conﬁne our intellectual thinking and restrict the eﬃcacy of our policy: the separation of intra- and intergenerational justice. Intergenerational justice deals with justice between the generations. Intragenerational justice focuses on lines of cleavage between contemporaries, such as economic disparities between states in the international system. On the one hand, the maxim that each generation has the right to act in a self-determining way has led to a political culture in which present generations pursue short-sighted and generationally speciﬁc objectives. By the same token, as Hans Jonas has argued, mankind’s realisation that his ability to transform nature for his own purposes may lead to irreversible environmental damage has led to the call for a new ethics for future generations. It is important to emphasise the pertinence this separation has outside the academic world: political decisions are often informed by only one type of justice, ignoring the consequences for other types of justices. On the other hand, proponents of the sustainability concept frequently take all types of justice into account and, by often implicitly assuming that they are complementary, ignore possible trade-offs. Hence one can ﬁnd a lack of intellectual endeavour focused on bridging the theoretical gap between the more traditional demands of social and international justice and intergenerational justice with real implications for policy.